PROBATION PERIOD IN THE INDIVIDUAL LABOUR CONTRACT - ADA HURBEAN; LAURA CETEAN-VOICULESCU (Challenges of the Knowledge Society)
This study wants to present the period of probation in the labour contract as an optional way to verify the sills of the employee, because of the Labour Code changes and from the view of the legal practice in this field. In fact, in actual labour relations, often, the work performed during the period of probation is consider performed outside of labour contract legal frame. Even more, period of probation appears, sometimes, as a unilateral manifestation of the employer’s will and it manifest itself as a resolutory condition of the contract and not as a forfeiture clause of this contract. All these led us to achieve a clear and thorough research of the probation period and of the specific employment relationship during the course of it.